Allelopathic potential of three forage legumes on three pasture weeds - da S. Souza Filho, Antônio Pedro; de A. Rodrigues, Luis Roberto; D. Rodrigues, Teresinha de Jesus (Pesquisa Agropecuaria Brasileira, 1997)
Bioassays were carried out to identify and characterize the allelopathic potential effects of forage legumes "leucena" (Leucaena leucocephala), "mineirão" (Stylosanthes guianensis cv. Mineirão) and "calopogônio" (Calopogonium mucunoides) on germination and radicle elongation of the pasture weeds "desmódio" (Desmodium adscendens), "guanxuma" (Sida rhombifolia) and "assa-peixe" (Vernonia polyanthes). Aqueous seeds and shoot extracts were prepared in a concentration of 10% (w/v). The pH and osmotic potential were measured in each extract. The effects of the osmotic potential on the results were calculated considering the regression equations adjusted to the variations of osmotic potential in each parameter and the osmotic potential of the extracts. The results showed that the pH did not constitute in a source of variation of the results. The donor species indicated allelopathic potential that varied in function of donor and receiver species and part of the donor plant. The aqueous shoot extract of "mineirão" and "calopogônio" showed inhibition potential higher than the extract from seeds, while for leucena the effects more evident were obtained with the extract from seeds. Comparatively, the radicle elongation was a more sensitive indicator than germination to the effects of the extracts. The receiver species "assa-peixe" was the less sensitive to the effects of the extract.
Keywords: allelopathy; seed; shoot; leucena; mineirão; Calopogonium; Desmodium; Sida rhombifolia; Vernonia polyanthes